KEWAJIBAN NEGARA TERHADAP PERLINDUNGAN TENAGA KERJA INDONESIA - WIRA PURWADI (MIMBAR YUSTITIA, 2021)
The problem of migrant workers working abroad is increasingly adding to the burden of labor problems in Indonesia, both concerning injustice in the treatment of labor dispatch, inappropriate placement, low salary standards because they are not in accordance with the agreed work contract, violence by labor users and harassment. sexual relations, the purpose of this study is to find out how the state's responsibility towards Indonesian workers abroad is. The research method uses normative research (labrary research) or library research related to statutory regulations. The results of the study indicate that the state has not been able to carry out the preamble of the fourth paragraph of the 1945 Constitution "to protect the entire nation" due to the unclear authority given by the state to the relevant institutions to be responsible for TKI abroad. . Juridically, the laws and regulations in the field of placement and protection of Indonesian Migrant Workers are not in sync vertically or horizontally.